Biogenic Silver Nanoparticles Decorated with Methylene Blue Potentiated the Photodynamic Inactivation of Pseudomonas aeruginosa and Staphylococcus aureus - Paramanantham Parasuraman; Thamanna R. Y; Chitra Shaji; Alok Sharan; Ali H. Bahkali; Helal F. Al-Harthi; Asad Syed; V.T. Anju; Madhu Dyavaiah; Busi Siddhardha (MDPI AG, 2020)
The persistence of multidrug resistance among microorganisms has directed a mandate towards a hunt for the development of alternative therapeutic modalities. In this context, antimicrobial photodynamic therapy (aPDT) is sprouted as a novel strategy to mitigate biofilms and planktonic cells of pathogens. Nanoparticles (NPs) are reported with unique intrinsic and antimicrobial properties. Therefore, silver NPs (AgNPs) were investigated in this study to determine their ability to potentiate the aPDT of photosensitizer against Staphylococcus aureus and Pseudomonas aeruginosa. Biologically synthesized AgNPs were surface coated with methylene blue (MB) and studied for their aPDT against planktonic cells and biofilms of bacteria. The nano-conjugates (MB-AgNPs) were characterized for their size, shape and coated materials. MB-AgNPs showed significant phototoxicity against both forms of test bacteria and no toxicity was observed in the dark. Moreover, activity of MB-AgNPs was comparatively higher than that of the free MB, which concludes that MB-AgNPs could be an excellent alternative to combat antibiotic resistant bacteria.